2021
DOI: 10.1186/s12885-021-08606-w
|View full text |Cite
|
Sign up to set email alerts
|

Overtreatment in nonmalignant lesions detected in a colorectal cancer screening program: a retrospective cohort study

Abstract: Background Although colorectal cancer (CRC) screening programs reduce CRC incidence and mortality, they are associated with risks in healthy subjects. However, the risk of overtreatment and overdiagnosis has not been determined yet. The aim of this study was to report the surgery rates in patients with nonmalignant lesions detected within the first round of a fecal immunochemical test (FIT) based CRC screening program and the factors associated with it. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The discernible difference between regions was based on the conducting of screening programmes (in regions without screening programmes, the surgery rates were higher) [ 61 , 62 ]. A different study, where surgery rates in patients with nonmalignant cancers had been analysed, showed the small value of the factor, and the surgical interventions had been performed mainly on the unresectable polyps [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discernible difference between regions was based on the conducting of screening programmes (in regions without screening programmes, the surgery rates were higher) [ 61 , 62 ]. A different study, where surgery rates in patients with nonmalignant cancers had been analysed, showed the small value of the factor, and the surgical interventions had been performed mainly on the unresectable polyps [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, LNPCPs containing covert malignancy are often removed piecemeal in the UK [9]. Worse still, if lesions are "overcalled" on assessment, patients with benign polyps may be subjected to unnecessary resectional surgery [10].…”
Section: Introductionmentioning
confidence: 99%
“…Overtreatment of colorectal tumors is a well-known risk. Patients with non-malignant adenomas may undergo partial colectomy, when polypectomy or mucosectomy would be less costly, less demanding for the patient, and have a lower rate of complications [ 9 , 10 ]. On the other hand, colonic tumors with an endoscopically benign appearance, commonly polypoid, are often removed by polypectomy or mucosectomy.…”
Section: Introductionmentioning
confidence: 99%